PENGARUH DISHARMONI KOMUNIKASI INTERPERSONAL ORANG TUA-ANAK DAN TEMAN SEBAYA TERHADAP TINGKAT KENAKALAN REMAJA (Studi di Kelurahan Kadipiro Surakarta) - Siswanta, Agnes Agung, Maya Sekar Wangi & (Transformasi, 2016)
The problem of juvenile delinquency is a social problem that can not be denied, a social issuerequired attention as alarming, because many of the juvenile delinquency cases suggestive ofevil. The rising trend in juvenile delinquency both in quality and quantity raises concerns manyparties, both public, government especially among parents and the community.The purpose of this study was to determine the effect of interpersonal communicationdisharmony parent-child and friend sebanya to juvenile delinquency in Kadipiro Surakarta.Thisstudy was based on the theory of interpersonal communication.This type of research is explanatory research. Research sites in Kadipiro Surakarta. The studypopulation was a teenager at Kadipiro aged between 15-19 years. Sample of 100 people withstratified random sampling technique. The type of data used primary data and secondary data.Data collection used questionnaire and literature. Data were analyzed used multiple linearregression.The results showed that the disharmony of the parent-child communication interpersonal hassignificant effect on juvenile delinquency. Peer group has significant effect on juveniledelinquency. The coefficient of the coefficient of determination (Adjusted R2) of 0.469 meansthat the contribution of variables influence interpersonal communication disharmony parentchildand peer influences amounted to 46.9%, while the remaining 53.1% is influenced by othervariables not studied, for example, is the media mass.The conclusion of this study is that there isan influence of disharmony interpersonal communication parent-child and friend sebanya tojuvenile delinquency, so it can be recommended for parents should supervise the behavior oftheir children outside the home so as not to get stuck into delinquency, as well as formingcommunication open between parents and children and for adolescents should follow thepositive activities such as lectures, extracurricularactivities so avoid delinquency.Key words: disharmony interpersonal communication, peers group, juvenile delinquency